Hoaks, Politik dan Risiko Masyarakat Modern - Jehamat, Lasarus; Jelahut, Yosef Emanuel; Damanik, Dasma A. (JAP UNWIRA, 2020)
Indonesia’s social space in the past year has been filled with the phenomenon of hoax. The phenomenon of hoax develops alongwith the strengthening and thickening of the national political axis. Society is not treated by true news but it is filled withvarious emotional outbursts. The implication is that the community is divided into small groups based on interests. This causesthe social and cultural space to be rigid and inflexible. By Ulrich Beck, such phenomena are called risk society. Risks arise notonly because of technological developments in physical reason but also because of erroneous social and political practices. In itsdevelopment, Indonesian politics follows the trend of thickening into groups. A society divided into groups has the potential tostrengthen internal integration. As a result, the level of external adaptation is low. Politics is called the most vulnerable regionand is therefore responsible for social divisions. Because of politics, elements of society make social media not only a tool butalso their ultimate goal. There, the people practice various news provocation movements the truth of which cannot be verified.Such reality demands state responsibility in managing the media. Media management is not the same as controlling media.Managing the media is providing literacy education not only to the media and the political elite but also to the general public.Consequently, the logical reasoning for the existence of a civilized Indonesian society should be honed contiously.
Keywords: hoax; risk society; politics; nation; society